Frequency of Helicobacter Pylori in Patients with Primary Open Angle Glaucoma - Muhammad Sufyan Aneeq Ansari, Faisal Mah, Zeeshan Khan, Oozeerkhan, Muhammad Arshad Mahmood, Mohamud Walid Peerbux (Pakistan Journal of Ophthalmology, 2019)
Purpose: To find out the frequency of Helicobacter pylori (H. pylori) antibody in the serum of people with established POAG. Study Design: Cross Sectional Study. Place & Duration of Study: LRBT Free Eye Hospital, Lahore from 1st July 2012 to 1st January 2013. Material and Methods: All patients attending the glaucoma unit of the outpatient department with primary open angle glaucoma willing to be included in the study were enrolled using consecutive sampling. After collecting demographic information of the patients 3 ml of venous blood was withdrawn. Later on processing was done using the chemiluminescent enzyme immunoassay of the Immulite 2000 systems analyzers H. pylori IgG detection kit. Quantitative variable such as age was presented as mean and standard deviation while qualitative variables such as gender and H. pylori status (positive or negative) were expressed as frequencies and percentages. Results: There were 100 patients included in the study with mean age of 50.45 ? 6.16 years. There were 49 (49%) male and 51 (51%) female patients. The mean antibody level of patients was 3.80 ? 2.57 with a range of 9.39. The minimum and maximum antibody level were 0.07 and 9.46 respectively. There were 75 (75%) patients having primary open angle glaucoma who were diagnosed positive with H. pylori. Conclusion: The study shows high frequency of H. pylori antibody in patients with Open Angle Glaucoma. Key Words: Optic Neuropathy, Open angle Glaucoma, Helicobacter Pylori.